The pathophysiology of alzheimer's disease - Freire, Dainara Silva; Silva, Aline Santana da; Borin, Fabiane Yamacita Yuri (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Farmácia, 2022)
Alzheimer's is a neurodegenerative disease that interrupts the synapse process between neurons, which causes memory lapses in the patient and an evolution of the symptoms until the patient dies. The cause of Alzheimer's disease is related to the accumulation of beta-amyloid peptide and other disorders that are still being studied and are alleviated by pharmacological administration. This article describes the pathophysiology of Alzheimer's Disease and some considerations on the application of Pharmacotherapy to more degenerative diagnoses. In addition to portraying the main aspects of this disease, its evolution and the forms of diagnosis and treatment.